TETUN LANGUAGE MAINTENANCE IN EAST TIMOR FORMER REFUGEE COMMUNITY - Rafael, Agnes Maria Diana (Sanata Dharma University, 2020)
This study was conducted with the aims of: (1) describing the use of Tetun Language in East Timor former refugees community Manusak village and (2) describing the factors of Tetun Language’s maintenance in Manuasak village. This research uses the sociolinguistic approach, the method used is descriptive qualitative method. The results of the study show that: (1) Tetun is still survives so far as it has migrated for 20 years from its native land. Of the 132 informants interviewed, 86.36% of informants used Tetun Language as a lingua franca with different age categories. For partner selection, 71.21% of informants use Tetun Language when communicating with family members and neighbors. Then 58% of informants use Tetun Language when communicating with family members, neighbors, and coworkers, while 21.21% of informants use the language when communicatin with family members, closest neighbors and game friends. The topics chosen were: (1) 59.09% of informants chose topic about daily life activities, 9.1% chose topics about daily life and some topics that are related to work, 14.4% of informants chose topics about daily life, economic topics, political topics, religious topics, and work topics, 6.81% of informants chose topics about daily life, topics about education, economic topics, political topics, topics about religion, and topics about work, and 10 , 60% of informants chose topics about daily life, topics about education, religious topics and work topics. For the domains of using Tetun Language, then Tetun Language is used in the family domain, neighborhood and at the workplace. Next are the factors caused the maintenance of Tetun Language: loyalty to mother tongue, pride in using Tetun Language , family supporting environment and regional conservation.